Literasi Kesehatan Mental pada Tenaga Kesehatan - Afifah, Kartika Anis, Dr. Nisa Rachmah N. A, M.Si, Psikolog, Setia Asyanti, S.Psi, M.Si, Psikolog (2016)
The aim of this study was to explore level of understanding of health workers in mental health. This study using action research approach, involving 32 informants consisted of midwives and nurses. Characteritics of the informants in this study is nurse or midwive in puskesmas (local government) Baki, aged 25-45 years old, and willing to participate in the study with informed consent. The study was conducted by using three kinds of methods: surveys, focus group discussions and interviews. These research was analyzed by triangulation technique. The results indicated informants ability to recognize mental disorder symptoms is still low. Informants have not implements knowledge of mental health, this matter can affected differences in assessment and patient care. Informants are not interested about mental health. Based on the study, it can be concluded that level of mental helth literacy on health workers is relatively low. This matter can affected to diagnosis process, patients treatments and care, it also can affect family to understanding condition, treatment and how to treat patients.